1998
DOI: 10.1177/1358836x9800300305
|View full text |Cite
|
Sign up to set email alerts
|

Reflex sympathetic dystrophy: facts and hypotheses

Abstract: Reflex sympathetic dystrophy (RSD) syndrome has been recognized clinically for many years. It is most often initiated by trauma to a nerve, neural plexus, or soft tissue. Diagnostic criteria are the presence of regional pain and other sensory changes following a noxious event. The pain is associated with changes in skin colour, skin temperature, abnormal sweating, oedema, and sometimes motor abnormalities. The clinical course is commonly divided into three stages: first (acute or hyperaemic), second (dystrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 64 publications
0
27
0
2
Order By: Relevance
“…Edema is a wellknown phenomenon in CRPS that can arise from such venous pooling and may increase after dependency of the affected extremity. 42 Moreover, the sympathetically mediated vasoconstrictor response during dependency is attenuated in patients with CRPS in the clinically affected and unaffected extremity, 43 and there are reports of increased capillary permeability in CRPS. 44 If the tilt-induced abnormal decrease in cardiac output in the patients was due to regional pooling in the affected extremity, the reduction should be highest in the patients with an affected lower extremity due to the greater venous system in the legs.…”
Section: Pain Medicinementioning
confidence: 99%
“…Edema is a wellknown phenomenon in CRPS that can arise from such venous pooling and may increase after dependency of the affected extremity. 42 Moreover, the sympathetically mediated vasoconstrictor response during dependency is attenuated in patients with CRPS in the clinically affected and unaffected extremity, 43 and there are reports of increased capillary permeability in CRPS. 44 If the tilt-induced abnormal decrease in cardiac output in the patients was due to regional pooling in the affected extremity, the reduction should be highest in the patients with an affected lower extremity due to the greater venous system in the legs.…”
Section: Pain Medicinementioning
confidence: 99%
“…It is theorized that sympathetic nerve fibers form connections with the injured peripheral nerve, which can then cause aberrant sensory stimulation. 6 For this reason, the subject performed the Southampton Hand Assessment Procedure 7 before, during, and after the implantation, and the subject's ability to perform 2-point discrimination was regularly assessed for signs of neuropathy. No perceivable loss of hand sensation or motion control was experienced by the subject, and regular testing after extraction has not indicated any measurable long-term defects other than minor scarring.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that CRPS-1 has clinical stages [25] and TPBS findings change according to clinical stages [15][16][17]. It was reported that F/P normalizes or even decreases, and afterward, DU normalizes as the disease progresses [15].…”
Section: Discussionmentioning
confidence: 99%